Portfolio: Hybrid Form, Bonny Cassidy, 2019 ... - Cassidy, Bonny (RMIT University, 2024)
Background - This folio is a development of form that I began in ‘grounds’ (2016) and ‘Hexham’ (2017), which applied lyric essay as a form to explore themes of colonisation. In this folio, published in 2019, I have sought to push formal experimentation further as a deepening of that theme. It is influenced by the lyric essays of Claudia Rankine and Natalie Harkin, and the prose poems of Alison Whittaker, which interrogate US and Australian black histories through a breakdown and reconstruction of creative form. Contribution - My recent hybridising of poetic and prose forms interrogates whiteness in Australia. It allows me to inhabit this theme through first-person voice, while deploying citation of broader contexts and sources. ‘Monument’ concerns public memorials in the process of Reconciliation, drawing on First Nations commentary as well as non-Indigenous voices and my own feelings about the materiality of a monument to colonial violence. ‘Cultural studs’ is a micro-essay on cultural gatekeeping, and the ...